Strategi, Implementasi, dan Peran Pengasuh dalam Pengembangan Pendidikan Agama di Pondok Pesantren Zainul Hasan Genggong Probolinggo - Uswatun Hasanah; Ainur Rofiq Sofa (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
Zainul Hasan Genggong Islamic Boarding School, founded in 1839, is one of the oldest pesantren (Islamic boarding schools) in Indonesia and plays a crucial role in educating the community and spreading Islamic teachings in the Probolinggo region. This study aims to analyze the strategies and implementation of religious education applied at this pesantren, focusing on the role of the caretakers (pengasuh) in determining policies and teaching methods within the pesantren environment. The research methodology includes interviews with relevant stakeholders, field observations, and a literature review related to the development of pesantren education. The results of the study indicate that Zainul Hasan Genggong applies a religious-based curriculum that integrates religious knowledge and life skills, with an active teaching approach. The caretakers of the pesantren play an important role in directing educational policies that align with the needs of the times, producing graduates who excel in religious fields and are ready to face global challenges.